Comparison of hydrolysis conditions to recover reducing sugar from oil palm fronds and rice straw / Norazlin Ismail - Ismail, Norazlin (2010)
A process for determining reducing sugar concentration from oil palm fronds and rice straw was developed. Reducing sugar of oil palm fronds and rice straw were determined in order to compare the hydrolysis conditions. In this study, oil palm frond and rice straw were pretreated with 2 M NaOH in order to obtained alkaline pretreated materials. Alkaline pretreated materials were then hydrolyzed with 1.0, 5.0 and 10.0% (v/v) sulfuric acid at 111 oC and 121 oC for 15 min and 30 min, respectively. The hydrolysate were analyzed for reducing sugar concentration by UV-Vis Spectrophotometer. The result showed that the maximum reducing sugar concentration of rice straw at 78.80 μg/ml was obtained after pretreatment with 2.0 M NaOH and hydrolysis with 1.0% (v/v) sulfuric acid at 111 oC for 30 min. Meanwhile, maximum reducing sugar concentration of oil palm frond was obtained at 81.11 μg/ml after pretreatment with 2.0 M NaOH and hydrolysis with 10%(v/v) at 121 oC for 30 min. In comparison, rice straw showed high reducing sugar concentration at low concentration of sulfuric acid. In contrast, oil palm frond showed high reducing sugar concentration at high concentration of sulfuric acid.